KEBIJAKAN KOREA SELATAN DALAM POLUSI UDARA LINTAS BATAS TIONGKOK - Rezqi, Jhanna Baitiez; Windiani, Reni; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
China has been trying to enhance their industry production in pursuit ofeconomic growth to overcome poverty in the region.In other hand, theindustrial growth have a negative impact on the environment, causing severeair pollution. Air pollution did not only hurt China but spread to SouthKorea’s region, which is causing problem to South Korea. This study aims tofind why South Korea did not protest related to China’s Transboundary AirPollution. The study uses qualitative research method with analythicdescriptive research type. The study results are.The Cooperation betweenChina and South Korea to reduce transboundary air pollution, both bilateraland multilateral are the Korea-China Environmental Cooperation Agreementdan the Korea-China Environmental Industry Investment Forum, TripartiteEnvironment Ministers Meeting (TEMM), Northeast Asian SubregionalProgram for Environmental Cooperation (NEASPEC), the Acid Depositionand Monitoring Network in East Asia (EANET) sand Long-rangeTransboundary Air Pollution in Northeast Asia (LTP), Northwest PacificAction Plan (NOWPAP), Northeast Asian Conference on EnvironmentalCooperation (NEAC) and Environment Congress for Asia and thePacific(ECO ASIA). Beside it,the main factor which is led South Korea didnot protest to China’s transboudary air pollution is economy factor.